Anti-Inflammatory Effects of a Methanol Extract from the Marine Sponge Geodia cydonium on the Human Breast Cancer MCF-7 Cell Line - Susan Costantini; Giovanna Romano; Fabiola Rusolo; Francesca Capone; Eliana Guerriero; Giovanni Colonna; Adrianna Ianora; Gennaro Ciliberto; Maria Costantini (Mediators of Inflammation)
Many research groups are working to find new possible anti-inflammatory molecules, and marine sponges represent a rich source of biologically active compounds with pharmacological applications. In the present study, we tested different concentrations of the methanol extract from the marine sponge, Geodia cydonium, on normal human breast epithelial cells (MCF-10A) and human breast cancer cells (MCF-7). Our results show that this extract has no cytotoxic effects on both cell lines whereas it induces a decrease in levels of VEGF and five proinflammatory cytokines (CCL2, CXCL8, CXCL10, IFN-γ, and TNF-α) only in MCF-7 cells in a dose-dependent manner, thereby indicating an anti-inflammatory effect. Moreover, interactomic analysis suggests that all six cytokines are involved in a network and are connected with some HUB nodes such as NF-kB subunits and ESR1 (estrogen receptor 1). We also report a decrease in the expression of two NFKB1 and c-Rel subunits by RT-qPCR experiments only in MCF-7 cells after extract treatment, confirming NF-kB inactivation. These data highlight the potential of G. cydonium for future drug discovery against major diseases, such as breast cancer.